STRENGTHENING LITERACY AND PSYCHOMOTOR SKILLS OF ADOLESCENTS IN FIRST AID FOR BLEEDING THROUGH PEC (PRESSURE-ELEVATION-COVER) TECHNIQUE SIMULATION - Rachmania, Diana; Widayati, Dhina (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: The adolescent age group is closely associated with high levels of physical activity, putting them at risk for injury, including bleeding. Therefore, proper first aid literacy and skills are essential through education and training. This community service activity aims to improve first aid literacy and psychomotor skills in bleeding among adolescents through education and training on PEC (Pressure-Elevation-Cover) techniques. Methods: The activity was carried out in July 2025 at Senior High School 1 Puncu involving 35 students of 5 students per class from 7 classes. The activity began with interactive education related to the concept of bleeding for 60 minutes and continued with training with a simulation approach using simple equipment on how to provide first aid for bleeding for 120 minutes with pressure techniques, and covering. Pre and post data for literacy were measured using questionnaires and observation sheets for psychomotor abilities. Results: An increase in the average literacy score (from 60 to 85) and psychomotor skills (most of the sufficient category became the majority in the good category). The results of statistical analysis using the Paired t-Test and Wilcoxon also showed a significant difference in literacy and skills pre and post with p = 0.001. Conclusion: Education and training using the PEC technique simulation method are effective in improving literacy and psychomotor skills in first aid for bleeding in adolescents. The simulation method provides hands-on experience in quickly and accurately performing first aid for bleeding. Similar activities can be conducted periodically with a broader target audience.